Characteristics of quasi-biennial oscillation over Kenya and their predictability potential for the seasonal rainfall - OGALLO , L.J .; OKOOLA, R. E.; WANJOHI, D. N. (MAUSAM, 1994)
investigated using monthly zo.ta l wind com ponents from Nairob i (Kenya ) within the period 1966-1987. RelatiHn.;;hips between the stra tospher ic eas terl y and westerly wino phases and t he seasona l ra infall anomalics were also iO\t,"..')t igatN. Res ults Irom spec tra l a nalysis indicated tho d ominance (If a 28 mon th s' period in the IllOal w ind comnoncn. The \'Crtical ra te of propagar ioa of both westerly and easterly wind phases was about - · 1.2 kmmonth. Results from statist ical analysis indicated signitica nr (at 5 '~~ level) association between rainfall anomaly class (above normal. normal. a mi below normal) and east erly and westerl y wind phas...es.